FUNGSI KANTOR PERTANAHAN SEBAGAI PELAKSANA PERCEPATAN PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) - Wa Ode Zamrud; La Ode Muhammad Muskur; Fitrian Fitrian (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2021)
This study aims to determine the function of the Baubau City Land Office as the implementer of accelerated complete systematic land registration (PTSL) and to determine the factors that hamper the function of the Baubau City Land Office as the implementer of the accelerated complete systematic land registration (PTSL). The data collected in this study are primary data and secondary data. To collect primary data, the autors used field research in two ways, namely: (1). Observation, namely directly going to the field to make observation in order to obtain the data needed both primary and secondary data .(2). Interview, which is data collection in the form of questions and andswers which is carried out directly to the respondent, in this case the Baubau City Land Authority, and all parties involved in the author’s research. Then what is meant by secondary legal material is carried out reviewing library materials relevant to research in the form of literature, scientific works ( research result), laws and regulations and related agencies. The data in this study were analyzed qualitatively, namely secondary data in the form of theory, definition and substance from various literatures, and laws and regulation, as well as primary data obtained from interviews, observation and field studies, then analyzed by law, theory and opinion relevant experts, in order to obtain a clear and complete picture so as to produce a conclusion that can be used to answer the problem formulation. Qualitative legal research methode is a systematic effort in legal research. Included in it are rules and techniques to satisfy the reseacher’s curiosity about a juridical phenomenon or how to find the truth in obtaining knowledge. So that in this study, generally assessing the symptoms or judicial facts under study does not use members, but simply uses quality or quality standards that are stated in words.